Code Integration, Data Verification, and Models Validation Using the ITER Integrated Modeling and Analysis System (IMAS) in EUROfusion. (16th November 2020) - Romanelli, M.; Coelho, R.; Coster, D.; Ferreira, J.; Fleury, L.; Henderson, S.; Hollocombe, J.; Imbeaux, F.; Jonsson, T.; Kogan, L.; Meneghini, O.; Merle, A.; et al.
Abstract: The ITER Integrated Modelling and Analysis System (IMAS) has been adopted by the EUROfusion Consortium as a platform to facilitate the analysis and verification of data from multiple tokamaks for the integration of physics codes and the validation of physics models for fusion plasma simulations. Data mapping tools have been developed to translate the tokamaks' native data format into IMAS. The mapping required the adoption of standard coordinates, conventions on direction of vectors, signs of fields, and harmonization of physics units. The mapped data have been verified by running integrated simulations using Kepler workflows. Results of the test using IMAS data are reported here along with an assessment of the system for present and future fusion applications.